Teks dan Konteks Ayat-Ayat Hisab Muhammadiyah - Muhammad Rifqi Arriza (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
The fact that the Koran is a divine word, has always been a magnet in itself for Muslims to always explore God's guidance in it. Scholars and scientists from various disciplines in every age have read it from various aspects. However, the Koran always proves that he will not be discussed by humans, not bound by place and time. One feature of reading the Koran is the interpretation approach. Interpretation itself has many features, ranging from analytical, thematic interpretations, seen from the aspects of fiqh, language, science, and so on.Keyword: Text, Context, Verses of Reckoning, Muhammadiyah.